RSD1 Is Essential for Stomatal Patterning and Files in Rice - Yu, Qi; Chen, Liang; Zhou, Wenqi; An, Yanhuang; Luo, Tengxiao; Wu, Zhongliang; Wang, Yuqi; Xi, Yunfeng; Yan, Longfeng; Hou, Suiwen (Frontiers in Plant Science, 2020)
Stomatal density is an important factor which determines the efficiency of plant gas exchange and water transpiration. Through forward genetics, we screened a mutant rice stomata developmental defect 1 (rsd1-1) with decreased stomatal density and clustered stomata in rice (Oryza sativa). After the first asymmetric division, some of the larger sister cells undergo an extra asymmetry division to produce a small cell neighbouring GMC. Some of these small cells development into stomata, which leads to stomatal clustering, and the rest arrested or development into pavement cell. After map-based cloning, we found that the protein encoded by this gene containing DUF630 and DUF632 domains. Evolutionary analysis showed that the DUF630/632 gene family differentiated earlier in land plants. It was found that the deletion of RSD1 would lead to the disorder of gene expression regarding stomatal development, especially the expression of STOMATAL DENSITY AND DISTRIBUTION1 (OsSDD1). Through the construction of OsSDD1 deletion mutants by CRISPR-Cas9, we found that, similar to rsd1 mutants, the ossdd1 mutants have clustered stomata and extra small cells adjacent to the stomata. OsSDD1 and RSD1 are both required for inhibiting ectopic ACDs and clustered stomata. By dehydration stress assay, the decreased stomatal density of rsd1 mutants enhanced their dehydration avoidance. This study characterized the functions of RSD1 and OsSDD1 in rice stomatal development. Our findings will be helpful in developing drought-resistant crops through controlling the stomatal density.